Modern Approaches to the Management of Children with Acute Obstructive Laryngitis and Epiglottitis - Aleksander A. Baranov; Nikolay A. Daikhes; Roman S. Kozlov; Leyla S. Namazova-Baranova; Irina V. Andreeva; Irina V. Artemova; Maiya D. Bakradze; Elena A. Vishneva; Mariya S. Karaseva; Olga V. Kаrneeva; Irina A. Kim; Olga P. Kovtun; et al. (Union of pediatricians of Russia, 2022)
Experts of the Union of Pediatricians of Russia have developed modern guidelines on the management of children with acute obstructive laryngitis and epiglottitis. Croup is the most common cause of acute upper respiratory obstruction in children aged from 6 months to 6 years. Usually respiratory viruses are the pathogenic agents of the disease. The etiological factor of epiglottitis is Haemophilus influenzae type b in the vast majority of cases (> 90%). However, nowadays, epiglottitis caused by this pathogen agent is more common in adults in countries with mass immunization against hemophilic infection. This article considers in detail etiology, pathogenesis, and classification issues. Special attention is given to diagnosis, differential diagnosis, and therapy (via evidence-based approach) of acute obstructive laryngitis in children.